2016
DOI: 10.1007/s10459-016-9718-1
|View full text |Cite
|
Sign up to set email alerts
|

A deeper look at implicit weight bias in medical students

Abstract: The Implicit Relational Assessment Procedure (IRAP, Barnes-Holmes et al. in Psychol Rec 60:527-542, 2010) was utilized as a relatively new tool to measure implicit weight bias in first- and third-year medical students. To date, only two studies (Miller et al. in Acad Med 88:978-982, 2013; Phelan et al. in Med Educ 49:983-992, 2015) have investigated implicit weight bias with medical students and both have found pro-thin/anti-fat implicit attitudes, on average, using the Implicit Association Test (IAT, Greenwal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 25 publications
0
50
0
Order By: Relevance
“…This may reduce student acceptance of the IAT results and may also cause considerable distress. Implications for educators, therefore, include the caveat to avoid forcing students into such categories [22]. Authors should discuss the results and how they can be interpreted in perspective of previous studies and of the working hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…This may reduce student acceptance of the IAT results and may also cause considerable distress. Implications for educators, therefore, include the caveat to avoid forcing students into such categories [22]. Authors should discuss the results and how they can be interpreted in perspective of previous studies and of the working hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the IAT was used to measure implicit bias or as a prompt for discussion and reflection. While 24 out of 38 articles used the IAT as a metric of bias [7, 3658], another 15 articles used the IAT as a stimulus to encourage discussion and reflection [8, 21, 5971] (one used the IAT for both) [7]. When used as a metric of implicit bias, the IAT was used to calculate the degree of implicit bias, and measure implicit attitudes in relation to an educational intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we cannot replicate the associations other studies of medical students have found between personal experiences with obesity, beliefs about the causes of obesity, and negative weight bias. [13][14][15][16] Finally, our study was not specifically designed to evaluate the "ethics and professionalism" session and its impact on students' attitudes toward obesity. If we had set out to do such a study, we would have collected postsession data from all cohorts immediately following the session and would have used more objective attitudinal measures than self-report.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicate that personal experiences with weight also contribute to medical students' negative attitudes and beliefs. [13][14][15] Perhaps counterintuitively, evidence suggests that medical students who themselves have successively struggled with overweight or obesity are more likely to hold negative attitudes toward patients with obesity than their counterparts who have regained lost weight. 13 Of particular concern is that medical students do not seem aware of their negative biases.…”
Section: Introductionmentioning
confidence: 99%